2009
DOI: 10.1016/j.ygyno.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in endometrial cancer cells by psammaplysene A involves FOXO1

Abstract: Objective-Endometrial cancer is the most common type of gynecologic cancer in the United States. In this study, we propose that a marine sponge compound, psammaplysene A (PsA) induces apoptosis in endometrial cancer cells through forced nuclear expression of FOXO1.Methods-Ishikawa and ECC1 cells were treated with varying doses of PsA. FOXO1 protein localization was observed using immunofluorescent staining of cells. The effects of PsA on cell viability and proliferation were assessed using a cell viability ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
(38 reference statements)
1
23
0
Order By: Relevance
“…Furthermore, decidualized tissue can grow in ectopic sites during pregnancy, resulting in deciduosis with a gross appearance that macroscopically mimics a malignant tumor [53]. In present study, we found that PA controls decidualization by dampening Akt-FoxO1 signaling pathway, which was observed in endometriosis and endometrial cancer patients group [59][60][61][62]. In this context, we are tempting to conclude that PA might be implicated in various endometrial disorders, such as deciduosis and endometriosis and subsequently fertility.…”
Section: Discussionmentioning
confidence: 46%
“…Furthermore, decidualized tissue can grow in ectopic sites during pregnancy, resulting in deciduosis with a gross appearance that macroscopically mimics a malignant tumor [53]. In present study, we found that PA controls decidualization by dampening Akt-FoxO1 signaling pathway, which was observed in endometriosis and endometrial cancer patients group [59][60][61][62]. In this context, we are tempting to conclude that PA might be implicated in various endometrial disorders, such as deciduosis and endometriosis and subsequently fertility.…”
Section: Discussionmentioning
confidence: 46%
“…Previous studies found that FOXO1 promotes apoptosis in many cell types and is suggested as a tumor suppressor [22], [24], [27], [28], [29]. It has been shown that FOXO1 is highly expressed in normal germinal center B cells and is not expressed in classical Hodgkin lymphoma (cHL), and ectopic expression of a constitutively active FOXO1 induces apoptosis in cHL cell lines and blocks proliferation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Berry et al . proposed that PsA induces apoptosis in endometrial cancer cells through increased expression of FOXO1 [15], a member of the Forkhead/winged helix family that plays a role in cell survival, cell cycle progression and oxidative-stress resistance [73]. These observations show diversified and dynamic activities of HDAC inhibitors on a broad spectrum of regulatory factors/pathways.…”
Section: Preclinical Studies On Hdac Inhibitors In Gynecologic Cancermentioning
confidence: 99%
“…Vorinostat was the first reagent to be approved by the US FDA for clinical use in 2006 [13,14]. Currently, a variety of established HDAC inhibitors and new compounds are being tested in cell culture and clinical trials of all phases [4,1517]. While most reagents are pan-HDAC inhibitors with unselective activities, several compounds are able to target a specific HDAC class or isoform.…”
mentioning
confidence: 99%